2017
DOI: 10.1371/journal.pone.0169519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Loading Duration and Short Rest Insertion on Cancellous and Cortical Bone Adaptation in the Mouse Tibia

Abstract: The skeleton’s osteogenic response to mechanical loading can be affected by loading duration and rest insertion during a series of loading events. Prior animal loading studies have shown that the cortical bone response saturates quickly and short rest insertions between load cycles can enhance cortical bone formation. However, it remains unknown how loading duration and short rest insertion affect load-induced osteogenesis in the mouse tibial compressive loading model, and particularly in cancellous bone. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 45 publications
6
53
0
Order By: Relevance
“…Trabecular bone has long been known to show a higher response to changes in the loading environment than cortical bone. This is a suggested effect of trabeculae having the ability to optimize load transfer because of the freedom to rearrange accordingly, and because of the more rapid remodeling rate of trabecular bone …”
Section: Discussionmentioning
confidence: 99%
“…Trabecular bone has long been known to show a higher response to changes in the loading environment than cortical bone. This is a suggested effect of trabeculae having the ability to optimize load transfer because of the freedom to rearrange accordingly, and because of the more rapid remodeling rate of trabecular bone …”
Section: Discussionmentioning
confidence: 99%
“…There were originally 10 Gorab Prx1 mice, but two mice died while under anesthesia during in vivo microCT scanning and therefore were excluded from the study. The proximal metaphyseal volume of interest (VOI) started 100 μm below the distal-most point of the growth plate and extended distally 10% of the tibial length (Willie et al, 2013; Yang et al, 2017). The cancellous and cortical bone in the metaphyseal VOI were segmented manually in the scans and analyzed separately.…”
Section: Methodsmentioning
confidence: 99%
“…The cancellous and cortical bone in the metaphyseal VOI were segmented manually in the scans and analyzed separately. The cortical midshaft VOI was centered at the midpoint of the tibia and extended 5% of the tibial length (Willie et al, 2013; Yang et al, 2017). A threshold of 671 mg HA/ccm was used to segment both diaphyseal and metaphyseal cortical bone.…”
Section: Methodsmentioning
confidence: 99%
“…Both tibiae were harvested and embedded in plastic. Diaphyseal transverse sections were cut at the site of strain gauge analysis (5 mm proximal to the distal TFJ), which corresponds approximately to a site 37% of the tibial length from the proximal end as described by others . (Unpublished data from our lab show that loading induces a similar bone formation response across the 25–50% tibial region.)…”
Section: Methodsmentioning
confidence: 99%
“…Protocols that use shorter daily loading bouts, fewer days/week, and shorter study length may be advantageous provided that they elicit a sufficient anabolic response. For example, the findings of Yang et al provide rationale for briefer daily loading (fewer cycles, no rest insertion). Regarding study length, initial studies of mouse axial loading used 2‐week (or longer) loading durations, yet more recent studies have reported significant loading effects in mice using only 3 or 5 days of loading .…”
mentioning
confidence: 99%